Laser Surface Processing of Hot Rolled Ni-45.0at.%Ti Shape Memory Alloy - Ma, Chengpeng (2018)
Both oxide removal and low surface roughness was achieved at hot rolled Ni-45.0at.%Ti shape memory alloy (SMA) surface using a nanosecond pulsed Nd:YAG laser. The oxidized and polished surfaces were analyzed by White-Light Interference (WLI), Focus ion beam (FIB) and energy dispersive spectrometer (EDS). Special attention was paid to investigate phase transformation evolution of SMA before and after laser irradiation using Differential scanning calorimeter (DSC) and X-ray diffraction (XRD). Results revealed that the as-received oxides with thickness of 10 micron had been removed completely after laser treatment, and surface roughness of laser-treated surface was less than 1μm. Moreover, no obvious change occurred for phase analysis and transformation temperatures of the SMA, indicating that the influence of laser irradiation on shape memory effect of hot rolled Ni-45.0at.%Ti SMA was negligible.